Biomization scores for the sites of the Tajik-Uzbek Surface Data Base - Lucas Dugerdil; Odile Peyron; Guillemette Ménot; Dilfuza Egamberdieva; Jakhongir Alimov; Suzanne A G Leroy; Eric Garnier; Arkadiusz Nowak; Sébastien Joannin (PANGAEA, 2025)
This table gathers the results of the biomization scheme, reconstructing biomes from pollen found at the TUSDB sites. The biomization method is given in Prentice et al. (1996) and the pollen type-to-plant functional type (PFT) and PFT-to-biome attribution follow the scheme given in Tarasov et al. (1998). The reconstructed biomes are Cold Deciduous Forest (CLDE); Cold Mixed Forest (CLMX); Cold Conifer Forest (COCO); Cold Desert (CODE); Cool Mixed Forest (COMX); Cold Steppe (COST); Hot Desert (HODE); Pioneer forest (PION); Taiga forest (TAIG); Temperate Deciduous Forest (TEDE); Tundra (TUND); Warm Mixed Forest (WAMX); Warm Steppe (WAST); Xerophytic Shrubland (XERO).
In: Dugerdil, L et al. (2025): Tajik-Uzbek Surface Data Base for modern pollen samples and vegetation plots: calibrations for functional diversity, climate and vegetation reconstructions in the past [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.979582